Progress in Structure and Function of GP5 Protein of Porcine Reproductive and Respiratory Syndrome Virus - Pu KANG; Mengpo ZHAO; Yuhao HUANG; Zongji LYU; Xiaohu WANG (Guangdong nongye kexue)
Porcine reproductive and respiratory syndrome (PRRS) is a highly contagious disease caused by porcine reproductive and respiratory syndrome virus (PRRSV). As an RNA virus, there are extensive variations in the genome of PRRSV, of which NSP2 and ORF5 genes are predominant. As the strains of different lineages have characteristic nucleotide sequences in ORF5, ORF5 can be used for the typing of PRRSV. ORF5 encodes the GP5 protein. GP5 protein contains multiple epitopes, which can interact with cellular receptors thus affect viral infection and replication. In recent years, molecular epidemiological investigations on PRRSV tend to reveal amino acid mutations unique to different strains. These mutations usually occur in the signal peptide coding region, non-neutralizing epitope, neutralizing epitope and transmembrane region of GP5 protein. Therefore, some studies have correlated these mutation data with the virulence and neutralization capacity of the virus. Some researchers tried to speculate about the conformational or functional changes in GP5 protein by mutation and explain this link from the structural basis of protein interaction. The tertiary structure of GP5 cannot be observed by traditional high-resolution cryo-EM and X-ray crystallography method, therefore, bioinformatics methods become the only option for related researches. In addition, GP5 can be used for the development of genetic engineering vaccines. This article reviews bioinformatics studies on GP5 protein in recent years, and summarizes the effects of GP5 protein on virus infection, replication, virulence and neutralization as well as the performance evaluation of GP5-based genetic engineering vaccines.